Continuidad o cambio tras el Covid-19 en el turismo de Ibiza y Formentera; Continuity or change after Covid-19 in tourism in Ibiza and Formentera - Joan-Carles Cirer i Costa (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The pandemic caused by Covid-19 has severely affected the tourism industry, but it has not equally affected all its segments or all the geographical spaces where it is carried out. Our objective is to determine whether it has caused structural changes in one of the major sun and beach tourist destinations in the Mediterranean: the islands of Ibiza and Formentera. To answer this question, we analyse the evolution of the prices offered by the different types of tourist accommodation on these islands in 2019, 2020 and 2021. This analysis shows that tourism practically disappeared on these islands in 2020, but when it partially recovered, in 2021, it did so with the same characteristics that existed before the pandemic.
Keywords: C12; D47; L11; L83; 330; COVID-19 impacts; Tourism recovery; Resilience; Hotel pricing; Ibiza and Formentera